Coxiella burnetii and the relationship with Q fever (Gaceta de Ciencias Veterinarias, 2022)
The purpose of this review was to expose the relationship between Coxiella burnetti and Q fever in various animal species. For this, the following aspects were covered: microorganism, epidemiology, pathogeny, public health, diagnosis, treatment, prevention and control. The main conclusion is that Q fever should be considered a public health problem.Keywords: Coxiella  burnetti, Q fever, molecular, serology, public health.